STUDI AWAL PROSES PEMBUATAN GLYCEROL TRIBENZOAT DARI GLISEROL DAN ASAM BENZOAT DENGAN MENGGUNAKAN KATALIS ASAM KLORIDA - A Abdurrakhman; Yanuar Rifianto; W Widayat (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Glycerol esterification process is one method that is widely in the conversion of glycerol. The product of conversion glycerol is environmentally friendly and renewable because it is not derived from petroleum. The products of the conversion of glycerol is commonly used in the food industry, cosmetics industry, polymer industry and can also be used as an additive for biodiesel which is also the compound before the glycerol formed. This study aims to examine the reaction of glycerol and benzoic acid using hidrochloric acid as catalyst. Experiments carried out by reacting glycerol and benzoic acid in stirred batch reactor with controlvariables are 100 rpm of stirrer speed, 500 ml volume (include glycerol, benzoate acid, and catalyst), and 60 minutes of reaction time. There are three random variables i.e. temperature of reaction 600C, 650C, 700C, mole ratio of acid to glycerol benzoate 3:1, 3.5:1, 4:1, and catalyst concentration (wt% glycerol) which is 5,32%, 7%, 8,68%. FTIR analysis results showed that the samples contained the results of IR spectra wavelength 1761 cm-1 in the fingerprint region and 3165 cm-1 frequency region group. The existence of these two adjustments that fixed in the area is strong evidence that the compound is Glycerol Tribenzoat.